“Communal skin”: contemporary art and protest masks (Altre Modernità, 2024)
Taking into account the idea of intercorporeality, the essay explores the use of masks – the particular attribute of many protest movements – in art projects of the Mongrel collective, the Pussy Riot, Jemima Wyman and Zach Blas, who rework them as a tool to create a collective identity that can help break down contemporary social inequalities of race, gender, class and sexual orientation. These artworks use masks to symbolically join or even ‘sew’ together protesters’ bodies, in order to create a hybrid anatomy that addresses socio-cultural differences from an alternative, non-hierarchicalizing perspective.
Keywords: intercorporeality; masks; Mongrel; Pussy Riot; Jemima Wyman; Zach Blas